(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2011)
Lower Murgabian (Roadian) beds have been discovered for the first time in a thick carbonate sequence ranging from Devonian to Triassic in the Hadim area, central Taurides, southern Turkey. The Roadian limestone consists of black algal fusuline packstone and black bioclastic packstone, and contains Presumatrina ciryi n. sp., an evolved form of the genus, Verbeekina erki n. sp., an earliest species of Verbeekina, Dunbarula protomathieui n. sp., an ancestral form of Dunbarula mathieui, and several smaller foraminifera.